2023
DOI: 10.1055/a-2019-0245
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Aspects of Prodromal Synucleinopathy Prognostic Counseling

Abstract: Alpha-synucleinopathies can be identified in their prodromal phase, raising several ethical issues. In this review, we first provide definitions of prodromal α-synucleinopathies and discuss the importance of distinguishing between prodromes and risk factors. Next, we discuss the implications of a diagnosis of prodromal α-synucleinopathy and considerations regarding prognostic counseling in both clinical and research settings. We review available data on patient preferences regarding disclosure as well as provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Based on these and previous results, 10,14-16,20,21,26,27 questionnaires and single question should not be used to diagnose RBD or to select patients with "probable RBD" to be included in future neuroprotective clinical trials. Due to the consequences of a false-positive RBD diagnosis based on screening questionnaires, not only for inclusion in research studies and clinical trials but also considering counseling and the important ethical implications of a diagnosis of iRBD 28 (ie, prodromal synucleinopathy), in line with the suggestion by Yao et al, 29 we believe that the term "probable RBD" should not be used to describe subjects screening positive for questionnaires. We found some differences in performance among the investigated RBD screening questionnaires.…”
Section: Discussionmentioning
confidence: 85%
“…Based on these and previous results, 10,14-16,20,21,26,27 questionnaires and single question should not be used to diagnose RBD or to select patients with "probable RBD" to be included in future neuroprotective clinical trials. Due to the consequences of a false-positive RBD diagnosis based on screening questionnaires, not only for inclusion in research studies and clinical trials but also considering counseling and the important ethical implications of a diagnosis of iRBD 28 (ie, prodromal synucleinopathy), in line with the suggestion by Yao et al, 29 we believe that the term "probable RBD" should not be used to describe subjects screening positive for questionnaires. We found some differences in performance among the investigated RBD screening questionnaires.…”
Section: Discussionmentioning
confidence: 85%
“…This approach is in line with a relational account of patient autonomy and with the model of shared decision making that has recently been proposed for iRBD prognostic counseling. 23 On the other hand, the "danger that misunderstandings and misappropriations of ideas derived from relational accounts could encourage the kinds of inappropriate paternalism" 46 exists. Therefore, studies investigating the patient and family perspectives are needed to understand whether this approach satisfies their needs and preferences, aspects that should be considered when developing educational programs and recommendations on risk disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…An ethical tension between the principles of respecting patient autonomy and nonmaleficence (avoiding harm) has often been emphasized, although some scholars have also underlined the role of the principle of beneficence. [11][12][13][14][15][16][17][18][19][20][21][22][23] Balancing these ethical principles, and with the objective of preserving the patient-physician relationship, there is an agreement that the patient should at least be informed of the association between iRBD and NDDs, and that the patient's preferences regarding further information should be investigated. 13,15,16,18,[20][21][22][23][24][25] Recent surveys found that most patients with iRBD want to receive information concerning their risk of developing an NDD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is now well-established by multiple studies published in the medical literature that up to 90% of patients ≥ 50 years old with iRBD will eventually develop an alpha-synucleinopathy, the important issues of prognostic counseling and ethical implications must be considered. A comprehensive review by experts on this topic (including one of the authors, CHS) has recently been published, 69 and will now be summarized. The most common ethical model for the physician-patient relationship is “shared decision-making”.…”
Section: Prognostic Counseling and Ethical Implications Regarding Irb...mentioning
confidence: 99%